(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Studies have established that rapport plays an important role in building a good relationship between the teacher and the student/s. It is also surely related to success in any learning process and ESL as well. This paper is designed to overview the role of rapport in learning English as a second language ESL and to understand how to build rapport in classrooms. Rapport is an important factor in determining the success or failure of any complex task. Besides, some related techniques are represented to help ESL teachers in building rapport with their students in order to meet good results of learning English. The reviewed literature indicated that rapport has a very important role in learning English as a second language. The paper concluded that rapport can be seen as a harmonious partnership that allows for productive communication, better results of work and fast resolution of problems.